2015
DOI: 10.2147/ppa.s75393
|View full text |Cite
|
Sign up to set email alerts
|

Patient–provider communication, self-reported medication adherence, and race in a postmyocardial infarction population

Abstract: ObjectivesOur objectives were to: 1) describe patient-reported communication with their provider and explore differences in perceptions of racially diverse adherent versus nonadherent patients; and 2) examine whether the association between unanswered questions and patient-reported medication nonadherence varied as a function of patients’ race.MethodsWe conducted a cross-sectional analysis of baseline in-person survey data from a trial designed to improve postmyocardial infarction management of cardiovascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…[3][4][5][6][7][8] However, to date, there is little information on its relationship with a wide range of healthcare outcomes of interest. In this study, we determine the association of PPC on patient-reported health status, measures of quality of care, healthcare resource utilization, and spending for a nationally representative sample of adults with established ASCVD in the United States.…”
Section: Okunrintemi Et Al Ppc and Outcomes Among Individuals With Ascvdmentioning
confidence: 99%
“…[3][4][5][6][7][8] However, to date, there is little information on its relationship with a wide range of healthcare outcomes of interest. In this study, we determine the association of PPC on patient-reported health status, measures of quality of care, healthcare resource utilization, and spending for a nationally representative sample of adults with established ASCVD in the United States.…”
Section: Okunrintemi Et Al Ppc and Outcomes Among Individuals With Ascvdmentioning
confidence: 99%
“…Researchers suggest that patient knowledge, self-monitoring, counseling, accountability, and a personalized program can contribute to improvement in medication adherence [ 52 ]. Experts and multiple stakeholders in medication adherence agree that a patient-centered approach is necessary, and increasing patient knowledge is critically important [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experts and multiple stakeholders in medication adherence agree that a patient-centered approach is necessary, and increasing patient knowledge is critically important [ 25 ]. Technological solutions have been suggested to alleviate medication nonadherence, such as mHealth technology, electronic monitors, pill-monitoring technology, online resources, and social media [ 52 ]. The best manner to engage with Veterans via text messaging and mobile apps has yet to be determined among those of different ages, sexes, chronic diseases, mobile phone usage patterns, and ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of patient–provider communication may directly affect patient adherence to treatment. Zullig et al 44 studied the perception of provider communication in a racially diverse group of adherent and nonadherent post-MI patients and asked whether the association of having unanswered questions with nonadherence varied by patients’ race. Overall, among the 405 patients in their sample, 232 (57.3%) were adherent, but only 63 of 140 (45%) minority patients were adherent.…”
Section: Patient Perceptionsmentioning
confidence: 99%